Prispevek k pojmu literarne identitete - Pogačnik, Jože (Traditiones (Ljubljana), 1997)
The paper attempts to define the contents and meaning of the concept of identity in literary science. The basis for the research is Cankar's drama "The Servants" (1910). The first part deals with the definition of the play's ideological and esthetic components, which received diametrically opposed responses from Slovene and Croat book and drama critics. An analysis of the value system in both literary environments reveals a number of interesting response constants - arising from a different unearths interesting material and gives a firm basis for discussing literary identity. The Slovene and Croat response to Cankar's drama reflects the autobiography of both nations and their national literature, not dwelling at all on the esthetic value of the drama, which is the object of a symptomatic collision at the time of the Moderna literary movement.
Keywords: Slovene literature; slovenska književnost; slovenska dramatika; literarne študije; identiteta; literarna recepcija; Cankar, Ivan: Hlapci